P224 The association between degree of airflow limitation and degree of coronary artery atheroma is not attributable to smoking history. (12th November 2015) - Ruickbie, S; Prasad, A; Jones, PW; Baker, EH
Abstract : Introduction: Prevalence of coronary artery disease (CAD) in chronic obstructive pulmonary disease (COPD) is 16–53% (Smith and Wrobel. Int J Chron Obstruct Pulmon Dis. 2014;9:871–888), with 25% COPD patients dying from cardiovascular disease. Diverse studies demonstrate 2-fold increased risk of CAD in COPD after adjustment for known cardiovascular risk factors. By contrast, in asthma increased CAD risk appears to be restricted to smokers (Colak et al . Am J Respir Crit Care Med. 2015 Apr 27). Our objectives were to investigate the association between airflow limitation and severity of coronary artery atheroma in patients undergoing coronary angiography and to determine the effect of smoking on this relationship. Methods: Patients attending for elective coronary angiography March–July 2015 underwent clinical assessment and spirometry prior to the procedure. Coronary artery disease burden was quantified from angiograms using the Gensini score (Needland et al. Am Heart J 164:547–552). A single rater (Professor of Interventional Cardiology), blinded to clinical diagnosis, determined number and severity of lesions. Blinded repeats were performed and ratings compared to clinical reports to ensure reliability. A nonlinear score was assigned to each lesion based on the severity of stenosis and a multiplier applied depending on lesion location in the coronary tree. Lesion scores were summed to derive total score, which was log-transformed for analysis. Results: 233 people (age 66 ± 10 years (mean±SD), 69% male) had FEV1 82 ± 21% predicted, FVC 89 ± 21% predicted, FEV1 :FVC ratio 73 ± 10%, Gensini median score 14 (IQR 6–33). On univariate analysis (Table 1 ), FEV1 and FEV1 :FVC were significantly and inversely correlated with Gensini score, but Gensini was not significantly associated with smoking status or pack year load. On multivariate analysis, neither airflow limitation nor smoking were significant determinants of Gensini. Conclusions: People with more severe airflow limitation have more coronary atheroma, but smoking does not appear to be a direct determinant of this relationship. Shared comorbid disease (e.g. dyslipidaemia) between COPD and CAD may be more important than smoking in determining the association, supporting the hypothesis that COPD and CAD are part of a multi-morbid disease complex. References: 1 Smith MC, Wrobel JP. Epidemiology and clinical impact of major comorbidities in patients with COPD. Int J Chron Obstruct Pulmon Dis . 2014;9 :871–88 2 Çolak Y, Afzal S, Nordestgaard BG, et al. Characteristics and prognosis of never-smokers and smokers with asthma in the copenhagen general population study. a prospective cohort study. Am J Respir Crit Care Med . 2015;192 :172–81 3 Neeland IJ, Patel RS, Eshtehardi P, et al. Coronary angiographic scoring systems: an evaluation of their equivalence and validity. Am Heart J 2012;164 :547–552.e1